ANALISIS PEMBELAJARAN JARAK JAUH DITINJAU DARI PENGALAMAN MENGAJAR GURU SELAMA PANDEMI COVID-19 - Julifahni, Shendy Avina; Muslihah, Neni Nadiroti; Permana, Hendra (caXra: Jurnal Pendidikan Sekolah Dasar, 2021)
The focus in this research is trying to explain 1) the implementation of distance learning in terms of the teacher's teaching experience 2) the effectiveness of distance learning. This study uses a qualitative approach with phenomenological methods, the subject is elementary school teachers grades 4-6. Data collection was carried out by interviewing and documenting the resource persons. Based on the results of the study, it was concluded that 1) the implementation of learning carried out by teachers was not optimal, this was due to planning related to learning objectives, as well as understanding and application of models, methods, techniques, media and evaluation tools that were carried out still feeling conventional without any innovations related to distance learning. far 2) the effectiveness of learning is said to have not been effective in its implementation because of several things such as a) students are not ready to carry out learning, b) less than optimal delivery of material c) student economic factors that affect the learning media used, and d) lack of student and parental responses related to teacher delivery.